The relationship between sleep quality and occupational well-being in employees: The mediating role of occupational self-efficacy - Peng, Jiaxi; Zhang, Jiaxi; Wang, Bingbing; He, Yanchen; Lin, Qiuying; Fang, Peng; Wu, Shengjun (Frontiers in Psychology, 2023)
Objective This study aimed to examine the impact of sleep quality on occupational well-being in employees by primarily focusing on the mediating role of occupational self-efficacy. Methods A total of 487 junior staff completed a set of questionnaires comprised Pittsburgh Sleep Quality Index scale, Occupational Self-efficacy Scale, and occupational well-being measurements. Results The results revealed that both sleep quality and occupational self-efficacy were significantly correlated with occupational well-being. The structural equation modeling analysis and the bootstrap test indicated that occupational self-efficacy partially mediated the effect of poor sleep quality on occupational well-being. Discussion These findings expand upon existing research on the relationship between sleep quality and well-being among occupational workers, shed light on the correlation of poor sleep quality with occupational well-being, and are valuable in promoting the occupational well-being of employees.